Clinical features of registry-ascertained alcohol use disorders that reflect familial risk. (1st July 2016) - Kendler, Kenneth S.; Ohlsson, Henrik; Edwards, Alexis C.; Karriker-Jaffe, Katherine J.; Sundquist, Jan; Sundquist, Kristina
Highlights: In a large epidemiological sample, we identified clinical features of Alcohol Use Disorder (AUD) cases that index familial risk. Early age at onset, number of registrations and recurrence predicted risk for AUD in relatives. This prediction was stronger for more closely related relatives consistent with these indexing genetic risk. Combing these indices, the highest decile of familial risk predicted risk for AUD in siblings 60% greater than that seen in the lowest decile. Abstract: Background: Alcohol Use Disorder (AUD) is clinically heterogeneous. Using a large epidemiological sample ascertained via public registries, is it possible to identify clinical and historical features of AUD that reflect familial risk? Methods: Using registration in national medical, legal or pharmacy registries, we identified four kinds of relative pairs (n = 683, 223) starting with a proband with AUD: cousins, half-siblings, full-siblings and monozygotic cotwins. Using linear hazard regression, we examined the interaction between five clinical/historical features of AUD in the proband and risk for AUD in these relatives. Results: Increased risk for AUD in relatives was predicted by the proband's early age at first registration, total number of registrations, recurrence, history of drug abuse and ascertainment in the medical versus the legal or pharmacy registry. In multivariate models, age at first registration, number of registrations, recurrence and history of drug abuse remained significant and in aggregate strongly predicted the risk for AUD in relatives. The risk for AUD in siblings of AUD probands in the highest decile of genetic risk predicted by these four indices was more than twice as great as that predicted in siblings of probands in the lowest risk decile. Conclusions: In an epidemiological sample, familial risk for AUD can be assessed by simple clinical and historical variables.